R1 and r2 Relaxivities of Dendrons Based on a OEG-DTPA Architecture: Effect of Gd3+ Placement and Dendron Functionalization. (22nd March 2015) - Fransen, Peter; Pulido, Daniel; Simón-Gracia, Lorena; Candiota, Ana Paula; Arús, Carles; Albericio, Fernando; Royo, Miriam
Abstract : In magnetic resonance imaging, contrast agents are employed to enhance the signal intensity. However, current commercial contrast agents are hindered by a low relaxivity constant. Dendrimers can be employed to create higher molecular weight contrast agents which have an increased relaxivity due to a lower molecular rotation. In this study, dendrimers containing DTPA derivatives as cores and/or branching units were used to chelate gadolinium ions. Locating the gadolinium ions inside the dendrimers results in higher relaxivity constants, possibly because the paramagnetic center is closer to the rotational axis of the macromolecule. The highest gain in relaxivity was produced by decorating the dendron surface with peptide sequences, which could be explained by the presence of more second-sphere water molecules attracted by the peptides. These findings could contribute to the development of more effective contrast agents, either by placing the paramagnetic gadolinium ion in a strategic position or through functionalization of the dendron surface.